Perilaku Kewargaan Organisasional di PT Pertamina (Persero) Jakarta - Darmawan Apriyadi; Novi Syahrianti; Wahyu Poncotoyo (Institut Transportasi dan Logistik Trisakti, 2019)
The purpose of the research is to find out and analyze the direct and indirect effect of characters or personalities with organizational citizenship behavior. The subject of the research is the pool transportation employees of PT Pertamina (Persero) Jakarta 2017. The research method was using survey with correlational approach and sample taken using simple random sampling technique. There are 50 employees and sample taken was 44 employees. There is a positive relation, on the research result, between characters or personalities with organizational citizenship behavior in pool transportation of PT Pertamina (Persero) Jakarta 2017.